Integrative anticoagulation of nafamostat mesylate in double plasma molecular adsorption system plus sequential half-dose plasmapheresis for patients with liver failure: a randomised controlled trial protocol - Lang Bai; Ling Zhang; Fang Wang; Yingying Yang; Juan Liao; Zhiwen Chen; Xiankun Sun (BMJ Open)
Introduction Nafamostat mesylate (NM) is widely recognised as a premier anticoagulant, especially in Japan and Korea. However, it has not yet been used as an anticoagulant in double plasma molecular adsorption system (DPMAS) plus sequential half-dose plasmapheresis (PE) therapy. This study aims to comprehensively evaluate the safety and efficacy of NM-integrated anticoagulation during DPMAS plus sequential half-dose PE therapy for patients with liver failure.Methods and analysis A two-arm, open-label, parallel, randomised controlled trial involving 132 patients with liver failure will be conducted in China. Eligible participants will be randomly allocated to either the nafamostat mesylate integrative anticoagulation group or the heparin integrative anticoagulation group, employing a central randomisation system at a 1:1 ratio throughout the course of DPMAS plus sequential half-dose PE therapy. The primary outcome includes the number of successfully completed DPMAS plus sequential half-dose PE therapy. The secondary outcomes include liver function indicators, extracorporeal circulation pressures, coagulation function parameters, all-cause mortality rates and survival rates. Clinical safety will be assessed by analysis of the number of bleeding events, the number of clotting events and adverse events. Outcome analyses will be performed on both the intention-to-treat population, which includes all patients randomised, and the per-protocol population, which includes eligible patients who adhere to the planned treatment and follow-ups.Ethics and dissemination The trial protocol was approved by the Biomedical Research Ethics Committee of West China Hospital of Sichuan University (approval number (2022)860). During the protocol revision process, all changes were reexamined and reapproved by the Biomedical Research Ethics Committee of West China Hospital of Sichuan University. The results will be presented at national and international conferences and published in peer-reviewed journals.Trial registration number ChiCTR2200064725.